Ethical and legal issues regarding the action and knowledge of orthodontists before civil liability - Luíza Valéria de Abreu Maia; Mariana Mourão de Azevedo Flores Pereira; Adriana Correia Pedro; Mário Marques Fernandes; Luiz Renato Paranhos (Universidade Estadual de Maringá, 2014)
This study evaluated the ethical and legal conducts of orthodontists regarding the professional/patient relationship, documentation used and degree of knowledge on the professional liability during the exercise of their specialty. This study sought to assess whether the time since graduation of the dentist as an expert interfered with their knowledge degree about the dental professional liability. The object population of the present study consisted of 56 dental surgeons, specialized in orthodontics, from the city of Belo Horizonte, Minas Gerais State, Brazil. The research was carried out using a survey addressed to these professionals, and descriptive statistics of the data. Chi-square test was used to check independence between factors and comparisons of proportions.  100% interviewed professionals request orthodontic documentation prior to the start of treatment; 71.5% request final documentation; 91% professionals affirmed they file this documentation; however, only 21.4% keep records for over 20 years; and most professionals (86%) use some sort of contract at the start of treatment, and a small percentage (30.4%) regard the liability of orthodontists as objective. It can be concluded that the interviewed professionals should acquire a higher level of knowledge regarding the professional liability and current legislation involving dental surgeons.